Production and Characterization of Collagenase From Bacillus sp. 6-2 Isolated From Fish Liquid Waste - Sartika Danial; Hasnah Natsir; Seniwati Dali; Leliani Leliani (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
Collagenases are enzyme that are able to hydrolyze native collagen into fragment collagen peptides. Collagenases and its hydrolysis products have received tremendous attention in medical and industrial applications. The present study was conducted to isolate and identify new collagenase producing bacteria from fish liquid waste, then produce and characterize collagenase. A total of 7 isolate from fish liquid waste were screened on selective medium containg 2 % collagen and its activity was confirmed by the formation of clear zone. Isolat 6-2 was positif as collagenase producer and identified as Bacillus sp. 6-2 by morphological and biochemical characteristics. The optimum fermentation time of enzyme was investigated. Collagenase crude extract was characterized by the effect of pH, temperature, and metal ions. Isolat 62 optimally produced collagenase enzyme after 30 h of incubation with activity of   0.072 U/mL and protein content of 3.768 mg/mL. The optimum pH and temperature were 7.0 and 40 oC, respectively. The enzyme was activated by 1 mM Ca2+and  Mg2+, and inhibited by   1 mM  Zn2+ and Co2+. Collagenase from Bacillus sp. 6-2 may have potentials for medical and industrial applications.